2006
DOI: 10.1088/1478-3975/3/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Active gels: dynamics of patterning and self-organization

Abstract: The actin cytoskeleton is an active gel which constantly remodels during cellular processes such as motility and division. Myosin II molecular motors are involved in this active remodeling process and therefore control the dynamic self-organization of cytoskeletal structures. Due to the complexity of in vivo systems, it is hard to investigate the role of myosin II in the reorganization process which determines the resulting cytoskeletal structures. Here we use an in vitro model system to show that myosin II ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
203
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(216 citation statements)
references
References 53 publications
13
203
0
Order By: Relevance
“…Actin filaments are compacted into dense clouds around large myosin foci and these actomyosin condensates then contract into larger superaggregates. The resulting structures are intrinsically three-dimensional (3D), in strong contrast to the more twodimensional (2D) aggregates reported previously, such as rings formed in fascin-bundled actomyosin systems (40) and vortices formed in actomyosin networks on surfaces (42). Although planar ring structures might relate to the vortex-like states predicted by active gel theories (29,31,43), such features are intrinsically 2D patterns and are topologically not possible in 3D (44).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Actin filaments are compacted into dense clouds around large myosin foci and these actomyosin condensates then contract into larger superaggregates. The resulting structures are intrinsically three-dimensional (3D), in strong contrast to the more twodimensional (2D) aggregates reported previously, such as rings formed in fascin-bundled actomyosin systems (40) and vortices formed in actomyosin networks on surfaces (42). Although planar ring structures might relate to the vortex-like states predicted by active gel theories (29,31,43), such features are intrinsically 2D patterns and are topologically not possible in 3D (44).…”
Section: Discussionmentioning
confidence: 75%
“…1B i). These rings are reminiscent of actin rings observed in the presence of skeletal myosin minifilaments and the actin bundler fascin (40). However, high-resolution images of the rings with only actin fluorescently labeled (to avoid spectral crosstalk with myosin) revealed that they were not composed of a continuous band of actin filaments, but rather of a collection of compact actin aggregates with a size below 1 μm (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These macroscopic approaches based on generic symmetry considerations predict the formation of diverse patterns in actomyosin gels such as asters and ring-like structures, which have been observed in studies in vitro (15).…”
mentioning
confidence: 94%